Hubungan Faktor Resiko dengan Mortalitas pada Pasien Rawat Inap Icu Covid-19 di Rumah Sakit Bp Kota Batam - Wennas Wennas; Tafsil Tafsil; Aldho Dharma Kamil (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2022)
Background: Corona Virus Disease-19 (COVID-19) causes a respiratory tract infection that was discovered in and declared a pandemic on March 11, 2020. Mortality in COVID-19 patients is known to be related to age and disease history. the greater risk of mortality obtained by patients who have a history of the disease coupled with older age, the older the age, the higher risk can apply mortality. Methods: This research method is descriptive analytic with a cross sectional study approach which was carried out at the Batam City Entrepreneurs Agency Hospital in December 2021. The sampling technique was simple random sampling with a total sample of 59 respondents. Univariate analysis is presented in the frequency distribution table and bivariate analysis using Chi Square . test. Results: Patients no cytokine storm was 62.7% and cytokine storm was 37.3%. No bronchopneumonia was 67.8%, and bronchopneumonia was 32.2%. No COVID-19 mortality is 64.4% and yes 35.6% mortality. There is a significant relationship between COVID-19 mortality and age in Batam City RSBP patients (p value = 0.000). There is a relationship between COVID-19 mortality and comorbidities in Batam City RSBP patients (p value = 0.000). There is a relationship between COVID-19 mortality and cytokine storm in Batam City RSBP patients (p value = 0.001). Conclusion: Based on this study, it was concluded that there was a significant relationship between the characteristics of the clinical picture and mortality in ICU COVID-19 inpatients at BP Hospital Batam in 2021.